Nuclear Transport Deficits in Tau-Related Neurodegenerative Diseases - Diez, Lisa; Wegmann, Susanne (Frontiers in Neurology, 2020)
Tau is a cytosolic microtubule binding protein that is highly abundant in the axons of the central nervous system (CNS). However, alternative functions of tau also in other cellular compartments are suggested, for example in the nucleus, where interactions of tau with specific nuclear entities such as DNA, the nucleolus, and the nuclear envelope have been reported. We would like to review the current knowledge about tau:nucleus interactions and lay out a new view of tau neurotoxicity based on (pathological) interactions of tau with the nucleus.